Construction of interactive Card Game as appliance for the learning in discipline Transport’s Systems in Civil Engineering course of Universidade Federal do Paraná - Bernardinis, Márcia de Andrade Pereira; Freitas, Matheus Silva; Costa, Rodolfo Augusto da; Araújo, Waldney Bruno Lima de (International Journal for Innovation Education and Research, 2015)
The objective of this research is to present and discuss the results with the inclusion of an educational alternative – Construction of Card Games – in order to enhance students learning in the discipline of Systems Transports in the Civil Engineering course of UFPR, when compared with classes that did not perform the activity. Through this discipline sought to assess if the students would be able, with the proposed approach, of absorb new knowledge and more interesting, without compromising the traditional programmatic content. For this, the decks were made in class times. The results, by the final ratings of discipline, when compared with three other classes in the same discipline, taught by other professors who did not develop the activities, show that this tool contributed in some way to the improvement of the traditional methodology, seen that among the groups showed the highest average compared to others, with positives results for learning.